Exposure to natural disaster and students' environmental awareness and perception of environmental terms - Trinidad, Jean Rose O. (2007)
The level of environmental awareness (LEA), the perception of environmental terms, and the image of the future of the environment of Grade 6 public elementary students who were exposed to natural disaster as compared to those students who were not exposed to natural disaster was explored in this study. It was also attempted to determine if gender affects LEA among the respondents. 53 Grade Six students from Central Real Elementary School, Real, Quezon comprised the group exposed to natural disaster while 59 Grade Six students from Padre Burgos Central Elementary school in a nearby town to Real comprised the group which was not exposed to any calamity in the last 20 years. Exposed students' understanding of terms is deeper than that of the not-exposed group and their examples were mpre concrete. It was revealed that their experiences during the natural disaster in the their area enhanced their perspective of the future.
Thesis (M.A. Environmental Education)--University of the Philippines, Diliman.
Keywords: Environmental education -- Philippines -- Real (Quezon).; Perception in children -- Philippines -- Real (Quezon).; Elementary schools -- Philippines -- Real (Quezon).